Heart failure care in the Central and Eastern Europe and Baltic region: status, barriers, and routes to improvement - Chioncel, Ovidiu; Čelutkienė, Jelena; Bělohlávek, Jan; Kamzola, Ginta; Lainscak, Mitja; Merkely, Béla; Miličić, Davor; Nessler, Jadwiga; Ristić, Arsen D; Sawiełajc, Lidia; Uchmanowicz, Izabella; Uuetoa, Tiina; et al. (ESC heart failure, 2024)
Despite improvements over recent years, morbidity and mortality associated with heart failure (HF) are higher in countries in the Central and Eastern Europe and Baltic region than in Western Europe. With the goal of improving the standard of HF care and patient outcomes in the Central and Eastern Europe and Baltic region, this review aimed to identify the main barriers to optimal HF care and potential areas for improvement. This information was used to suggest methods to improve HF management and decrease the burden of HF in the region that can be implemented at the national and regional levels. We performed a literature search to collect information about HF epidemiology in 11 countries in the region (Bulgaria, Croatia, Czechia, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Serbia, and Slovenia). The prevalence of HF in the region was 1.6-4.7%, and incidence was 3.1-6.0 per 1000 person-years. Owing to the scarcity of published data on HF management in these countries, we also collected insights on local HF care and management practices via two surveys of 11 HF experts representing the 11 countries. Based on the combined results of the literature review and surveys, we created national HF care and management profiles for each country and developed a common patient pathway for HF for the region. We identified five main barriers to optimal HF care: (i) lack of epidemiological data, (ii) low awareness of HF, (iii) lack of national HF strategies, (iv) infrastructure and system gaps, and (v) poor access to novel HF treatments. To overcome these barriers, we propose the following routes to improvement: (i) establish regional and national prospective HF registries for the systematic collection of epidemiological data; (ii) establish education campaigns for the public, patients, caregivers, and healthcare professionals; (iii) establish formal HF strategies to set clear and measurable policy goals and support budget planning; (iv) improve access to quality-of-care centres, multidisciplinary care teams, diagnostic tests, and telemedicine/telemonitoring; and (v) establish national treatment monitoring programmes to develop policies that ensure that adequate proportions of healthcare budgets are reserved for novel therapies. These routes to improvement represent a first step towards improving outcomes in patients with HF in the Central and Eastern Europe and Baltic region by decreasing disparities in HF care within the region and between the region and Western Europe.
Keywords: Europe, Eastern; Baltic States; Prevalence; Quality Improvement; management nemoci; morbidita; Humans; zlepšení kvality; lidé; srdeční selhání; východní Evropa; Heart Failure; Morbidity; Evropa; Disease Management; Europe; pobaltské republiky; prevalence